Novel binary/multilevel Manchester based modulation technique for high-speed communication systems - Oluwajobi, Festus Idowu (2020)
A new advanced modulation format based on Manchester signalling was proposed and assessed for high-speed optical communication systems. This new advanced modulation format called Modified Manchester (MM) was derived from the combination of Manchester and Vestigial-Sideband (VSB) techniques. Its performance was assessed and compared in terms of spectral efficiency, chromatic dispersion tolerance and receiver sensitivity against Conventional Manchester (CM), Return-to-Zero (RZ) and Non-Return-to-Zero (NRZ). The spectral efficiency of the MM was enhanced by 31.3% due to the optimisation of the optical filter employed for VSB filtering. Therefore, the dispersion tolerance of MM is140 ps/nm, which is three times more than that of CM of 44 ps/nm and twice more than that of NRZ of 51.8 ps/nm and better than RZ with dispersion tolerance of 109 ps/nm at the BER of 10-9. The improvement performance was achieved without the utilisation of any dispersion compensation module or electronic equalisation. The research also examined the transmission performance of the MM modulation scheme over wavelength division multiplexing (WDM) system and compared with the CM format at the bitrate of 10 Gb/s per channel. Where MM has a better performance compared to CM in terms of tolerance against narrow optical filtering, spectral efficiency (improved by 32%) and chromatic dispersion tolerance (improved by +100 ps/nm). Sixteen wavelength channels (16 x 10 Gb/s) are modulated to provide 160 Gb/s data capacity which was successfully transmitted over 224 km standard single mode fibre (SSMF) using MM while the CM range is approximately 157 km.